ARTEMISIA ANNUA: SELECTION FOR HIGH ARTEMISININ YIELDING LINES FOR PRODUCTION IN SUB-SAHARAN AFRICA - Simon, J. E.; Park, C.; Wu, Q. L.; Diatta, M.; Diouf, B.; Asante-Dartey, J.; Acquaye, D.; Quansah, C.; Akromah, R.; Giblain, C.; Gbewonyo, K.; Ferreira, J. F. S.; et al. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Malaria continues to be a major infectious disease facing those living in tropical regions of the world. Use of artemisinin-combination treatments (ACT) as the first line treatment for multi-drug resistant falciparum malaria relies on derivatives of artemisinin, a natural product from Artemisia annua. Major commercial production regions include China, Vietnam and East Africa (Tanzania/Kenya). While several challenges face new producing regions, our work focuses on developing high yielding lines for sub-Sahara Africa for co-development with source countries. Our germplasm grown in several African countries appears to be non-photoperiodic, high yielding with artemisinin >1.% dry leaf wt. The parent populations from which the selections and progeny were derived came originally from UNICAMP. Highest yielding SPS were vegetatively cloned, and further selections made in the USA and Africa. Field trials established in Ghana, Madagascar, Senegal and South Africa identified lines adaptable to local conditions. Results showed that selection and testing for artemisinin in one location held relatively stable when the plants were evaluated in other regions. Generally, lines with the highest artemisinin remained high across the countries evaluated. Greatest environment impact was observed on biomass accumulation. Further selections conducted in Africa led to improvements in plant growth form, with some reaching heights of 2 m. Advanced lines field grown in sub-Sahara Africa contained artemisinin concentrations >1.0% reaching as high as 1.7% (dry leaf wt) and appear promising for varietal co-development in Africa. No problems relative to collecting viable seeds were observed in any country, stability of seed progeny remain to be tested.